Strategi Reinventing Government dalam Pengembangan Pariwisata pada Dinas Pariwisata Kota Tanjungpinang - Yana Wardani, Ratika; Subiyakto, Rudi; Okparizan, Okparizan (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
The tourism sector plays a crucial role in economic growth by increasing the country's foreign exchange and creating jobs. Indonesia, with more than 17,000 islands rich in natural and cultural beauty, has great tourism potential. Riau Islands Province, especially Tanjungpinang City, has significant natural and cultural tourism potential. This research aims to analyze the application of the concept of reinventing government in developing Tanjungpinang tourism by increasing management efficiency and innovation in the tourism bureaucracy. This research uses qualitative methods with data collection techniques through observation, interviews and documentation. The research results show that the application of the principles of "Reinventing Government" such as catalyst government, community-owned government, competitive government, mission-oriented government, results-oriented government, customer-oriented government, entrepreneurial government, anticipatory government, and decentralized government, has had a positive impact in developing tourism in Tanjungpinang. The conclusion shows that collaboration between government, society and the private sector is the key to success, and improving service quality and innovation are the main factors in attracting tourists and increasing regional income. These results indicate that the reinventing government approach can be an effective model for tourism development in other cities.